2022
DOI: 10.1039/d1qi01422f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structures of fluoride-bridged dysprosium clusters: influence of fluoride ions on magnetic relaxation behaviors

Abstract: The synthesis of the fluoride-bridged tri- ([{Cp’2Dy}{μ-F}]3·tol, 1Dy3, Cp’ = C5H4Si(CH3)3; tol = toluene), tetra- ([{Cp’2Dy(μ-F)2}2{(Cp’)(THF)Dy(μ-F)}2]·hex, 2Dy4, THF = tetrahydrofuran; hex = n-hexane),and hepta-nuclear (3Dy7) dysprosium complexes are reported here...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…On the other hand, the exchange interactions ( J ex ) are antiferromagnetic and weaker, though within the same order of magnitude compared to the dipolar interactions. The extracted J ex values align with several dinuclear dysprosium complexes, accounting for the pseudospin S = 1/2 of Dy 3+ ions. ,,, When scaled for a m J = 15/2 state, the exchange interactions are expected to be considerably lower, as expected for lanthanide systems. Regarding the observed differences in the magnetic exchange coupling, the latter depends on several parameters beyond just the intramolecular Dy 3+ –Dy 3+ distance.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, the exchange interactions ( J ex ) are antiferromagnetic and weaker, though within the same order of magnitude compared to the dipolar interactions. The extracted J ex values align with several dinuclear dysprosium complexes, accounting for the pseudospin S = 1/2 of Dy 3+ ions. ,,, When scaled for a m J = 15/2 state, the exchange interactions are expected to be considerably lower, as expected for lanthanide systems. Regarding the observed differences in the magnetic exchange coupling, the latter depends on several parameters beyond just the intramolecular Dy 3+ –Dy 3+ distance.…”
Section: Resultssupporting
confidence: 65%
“…This has been recently exemplified in dilanthanide complexes showing metal–metal bonding and exhibiting giant coercive field of at least 14 T . Obviously, dinuclear complexes represent therefore the simplest model to probe the influence of magnetic interactions on the slow relaxation dynamics. ,, …”
Section: Introductionmentioning
confidence: 99%
“…To explore the magneto-structural correlations of tetranuclear Dy III -based SMMs, this class of complexes were summarized (Table S13). The nuclear centers of tetranuclear Dy III complexes have various shapes such as linear, cymbiform, and parallelogram. (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Gao et al reported three Cp-based Dy-F clusters where fluoride ions affect the orientation of the principal magnetic axis of the ground Kramers doublet of the individual Dy(III) ion and the exchange interactions between the Dy(III) ions. 19 In general, polydentate ligands are essential to prepare an air-stable SMM with fluoride ligands as they not only stabilize the molecular skeleton but also leave a suitable space for the coordination of fluoride ions to the metal center, such as 1,4,7,10-tetrakis(2-pyridylmethyl)-1,4,7,10-tetraaza-cyclododecane, 20 tris(3-(2-pyridyl)pyrazolyl)hydroborate, 21 Schiff-base hexaazamacrocycles etc. 22 Indeed, we have reported two chiral macrocyclic mononuclear Dy(III) compounds featuring terminal fluoride coordination.…”
mentioning
confidence: 99%
“…Recently, Gao et al reported three Cp-based Dy–F clusters where fluoride ions affect the orientation of the principal magnetic axis of the ground Kramers doublet of the individual Dy( iii ) ion and the exchange interactions between the Dy( iii ) ions. 19…”
mentioning
confidence: 99%